Long-term antibody dynamics challenge the paradigm of lifelong homotypic immunity to dengue virus - Jair Andrade; Adrien Mitard de Girardier; Angkana T. Huang; Darunee Buddhari; Marco Hamins-Puertolas; Maria-Theresa Alera; Mary Noreen Chua; Taweewun Hunsawong; Derek A. T. Cummings; Stephen Thomas; Heather Friberg; Jeffrey R. Currier; et al. (Proceedings of the National Academy of Sciences, 2026)
Immunity following infection with the four dengue virus serotypes (DENV1-4) remains difficult to define. Reports of individuals being reinfected with the same serotype challenge the paradigm that infection induces lifelong homotypic immunity. However, the frequency of these events and their importance for shaping immune profiles remain unknown. Here, we used data from three cohorts (N = 4,268 total participants) in two highly endemic settings (Cebu, Philippines, and Kamphaeng Phet, Thailand), which included long-term follow-up of individuals (mean follow-up of 8.8, 1.9, and 5.0 y). These data allowed us to elucidate age-specific patterns of infection and immunity, and to quantify individual long-term antibody titer dynamics following infection. We formulated mathematical models to explain these patterns, allowing for the possibility of progressive loss of immunity to homotypic reinfection. At the individual level, we found that, in the absence of subsequent infection, antibody titers exhibit a steady long-term decay following incident infections (half-life of 7 to 8 y), with the rate of decay slowing with increasing age. At the population level, incorporating homotypic reinfection was required to explain the age-specific dynamics of infection and immunity observed in our cohorts. We estimated that in highly endemic settings such as the Philippines, 60% of individuals have been homotypically reinfected by the age of 40 y. Our findings highlight homotypic reinfections as a key feature of endemic DENV settings and suggest that vaccines mimicking natural infection might not be expected to provide lifelong protection against infection.